The Coordination between Arabic Studies Programs and Job Prospects for Undergraduate and Postgraduate Students in Chennai City - K M A AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
In the rapidly evolving landscape of education, it's essential to adapt strategically to changing trends and job opportunities for graduates. The Master's Program in Arabic Language is taking proactive steps to ensure the curriculum remains relevant to the demands of the job market. This study aims to assess the alignment between the curriculum and job requirements for graduates and postgraduates, the time taken to secure employment, the skills utilized in Arabic teaching roles, and the adequacy of the curriculum in preparing graduates for the challenges of the professional world. Utilizing a qualitative descriptive approach, data was gathered from alumni and employers between 2018 and 2022 through questionnaires, interviews, and group discussions. Analysis of the data revealed that 69.9% of graduates found their work aligned with the curriculum, with 39.2% working as Arabic language teachers, 20.3% in Computer, Media and MNC Companies and 28.4% are working outside the education sector. The average time to secure employment was less than six months, with technology-based teaching skills being the most impactful. Recommendations include adapting the curriculum to embrace technology in Arabic teaching, enhancing research methodology, and encouraging publication of articles and books to meet the demands of the digital era and the labour market.